2013
DOI: 10.5588/ijtld.12.0480
|View full text |Cite
|
Sign up to set email alerts
|

Social, economic, and psychological impacts of MDR-TB treatment in Tijuana, Mexico: a patient's perspective

Abstract: Setting The state of Baja California, Mexico had the highest prevalence of multidrug-resistant tuberculosis (MDR-TB) in Mexico in 2009. Objective To understand the socioeconomic burdens of MDR-TB disease and its treatment on patients in Tijuana and Mexicali, Mexico. Design From July to November 2009, qualitative interviews were conducted with 12 patients who were enrolled in a US-Mexico binational MDR-TB treatment program called “Puentes de Esperanza” (Bridges of Hope), which was designed to support MDR-TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 8 publications
3
71
0
11
Order By: Relevance
“…Patients with longer period of illness experienced higher degree of depression. Reason may include hopelessness, sense of worthlessness, hospitalization, social stigmatization and loss of earning all these factors lead to self-depreciation, conscious and unconscious fear of ailment and death [32,33]. Our study showed positive relation of depression with past treatment outcome and previous use of SLDs.…”
Section: Discussionsupporting
confidence: 50%
“…Patients with longer period of illness experienced higher degree of depression. Reason may include hopelessness, sense of worthlessness, hospitalization, social stigmatization and loss of earning all these factors lead to self-depreciation, conscious and unconscious fear of ailment and death [32,33]. Our study showed positive relation of depression with past treatment outcome and previous use of SLDs.…”
Section: Discussionsupporting
confidence: 50%
“…These findings corroborate the findings from other studies, which have highlighted the psychological, social and economic challenges experienced by MDR-TB patients. 7 This result warrants a comprehensive intervention plan to address these issues in a phased manner in order to enhance treatment adherence and better quality of life among MDR-TB patients.…”
Section: Discussionmentioning
confidence: 99%
“…consultations), direct non-medical expenses (e.g. transport and food for accessing health services) and lost income from time off work related to disability, discrimination and/or infection control laws [2]. With the treatment duration for drug-resistant TB lasting up to 24 months, affected households are especially vulnerable to TB-related costs [1].…”
mentioning
confidence: 99%